Maternal Near Miss : A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
The term Maternal Near Miss (MNM) refer to women who have escaped death either by chance or due to good health care after experiencing severe life threatening complication during pregnancy, labour and within six weeks after termination of pregnancy. A Near Miss event in a 3rd gravid at 42 weeks with intrauterine death having intractable Post Partum Haemorrhage (PPH) with severe maternal morbidity is reported here. Delay means death holds true for such emergency situation. The aim of the report is to stress the need of patients education, importance of emergency transportation and availability of multi-disciplinary tools and adequate blood transfusion at all level of health care system. Severe Acute Maternal Morbidity (SAMM) is a complement for maternal mortality and also to evaluate the quality of obstetric care in that particular institution. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22889 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 67-70